2021
DOI: 10.15420/aer.2021.30
|View full text |Cite|
|
Sign up to set email alerts
|

Electro-energetics of Biventricular, Septal and Conduction System Pacing

Abstract: Abnormal electrical activation of the ventricles creates abnormalities in cardiac mechanics. Local contraction patterns, as reflected by strain, are not only out of phase, but also show opposing length changes in early and late activated regions. Consequently, the efficiency of cardiac pump function (the amount of stroke work generated by a unit of oxygen consumed), is approximately 30% lower in dyssynchronous than in synchronous hearts. Maintaining good cardiac efficiency appears important for long-term outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…[ 27 ] It has been reported that the efficiency of cardiac pump function (the amount of stroke work generated by a unit of oxygen consumed) is approximately 30% lower in dyssynchronous than in synchronous hearts. [ 28 ]…”
Section: Pathophysiology Of Pacing-induced Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 27 ] It has been reported that the efficiency of cardiac pump function (the amount of stroke work generated by a unit of oxygen consumed) is approximately 30% lower in dyssynchronous than in synchronous hearts. [ 28 ]…”
Section: Pathophysiology Of Pacing-induced Cardiomyopathymentioning
confidence: 99%
“…27 It has been reported that the efficiency of cardiac pump function (the amount of stroke work generated by a unit of oxygen consumed) is approximately 30% lower in dyssynchronous than in synchronous hearts. 28 As a result of non-physiological RV pacing, changes in ventricular blood perfusion, neurohumoral innervation and fatty acid metabolism have also been observed. Moreover, dyssynchrony results in changes in local myocardium oxygen demand.…”
Section: Pathophysiology Of Pacinginduced Cardiomyopathymentioning
confidence: 99%
“… 16 However, it has been found that the degree of dyssynchrony measured by time-to-peak shortening, strain patterns, or internal stretch fraction in conduction system pacing is moderate and nearly similar to that in physiological conduction and less than that observed in RVP. 17 …”
Section: Introductionmentioning
confidence: 99%